Five times faster rethinking the science, economics, and diplomacy of climate change - Sharpe, Simon ca. 20./21. Jh (Cambridge University Press, 2025)
We need to act five times faster to avoid dangerous climate change. This is an inside story from Simon Sharpe, who has spent ten years at the forefront of climate change policy and diplomacy. In our fight to avoid dangerous climate change, science is pulling its punches, diplomacy is picking the wrong battles, and economics has been fighting for the other side. This provocative and engaging book sets out how we should rethink our strategies and reorganise our efforts in the fields of science, economics, and diplomacy, so that we can act fast enough to stay safe. This edition has been brought up-to-date throughout, and includes a new chapter on how international cooperation on climate change can be reconciled with economic and geopolitical competition. It also includes a response to the question the book has most often provoked: 'How can I help?'